(untitled) (E Conference Zone, 2022)
Currently, in our country, some specialists in the field of physical education, searching for a way out of the current crisis situation, propose to increase the volume of compulsory physical education classes at the university. However, such a path is unacceptable, since it requires significant material and financial investments aimed at intensive construction of sports facilities, training of professional personnel, and significant changes in the curricula for training specialists with higher professional education. A more promising direction in solving the identified problems of physical education of students, according to the majority of scientists and teachers of higher education, is the scientific development and justification of innovative forms of scheduled classes in universities, taking into account the interests and needs for physical culture and wellness classes